Foreign Direct Investment and CO2, CH4, N2O, Greenhouse Gas Emissions: A Cross Country Study - Paul, Sujan Chandra; Rosid, Md. Harun Or; Sharif, Md. Jamil; Rajonee, Anjuman Ara (International Journal of Economics and Financial Issues, 2021)
To investigate the effects of foreign direct investment on CO2, CH4, N2O, and other greenhouse gas emission the study was conducted. The panel data from 200 countries were collected for the period of 1990 to 2018. Ordinary Least Square (OLS), Pooled Ordinary Least Square (POLS), Driscoll-Kraay (DK), Second Stage Least square (2SLS), Generalized Methods of Moments (GMM) model has been performed. The findings showed that foreign direct investment has positive impact on CO2 in all the models. The study also showed that FDI had negative impact on CH4 emission and positive impact on N2O emissions in all models except GMM model. Finally, FDI had mixed impact on greenhouse gas emission but the results were statistically insignificant except OLS model. Keywords: CO2, CH4, N2O, Greenhouse Gas emission, FDI JEL Classifications: F21, O44, Q5 DOI: https://doi.org/10.32479/ijefi.11535